Desenvolvimento profissional docente na EAD: um olhar sobre a experiência de professores e tutores a distância - SILVA, Ketiuce Ferreira (2014)
This study belongs to the line of research Teacher Education and Digital Culture, and its main objective was to understand the context that permeates the teacher professional development of teachers and tutors, who work in an Education course in the distance modality. The specific objectives were to present foundations that direct teaching in Distance Education (DE); analyze documents which regulate the distance Education course offered by a public institution of undergraduate education in the state of Minas Gerais; define the profile of teachers and tutors, who act in this course, as well as to describe the position of these individuals front to issues that concern their professional development; and identify contributions that may constitute a reference for teacher professional development in DE. The research context was a Distance Education Course, offered by a public undergraduate education institution in the state of Minas Gerais, under the Open University System of Brazil. The study subjects were teachers and tutors, who act in that context. The investigative path was guided by three discussions: in which context is teaching in DE embedded? What are the specific characteristics of teaching in DE? How has teacher education been for DE and what individual, collective and institutional initiatives can be observed and/or suggested by teachers of distance education concerning their professional development? To achieve the proposed objectives, it was adopted qualitative approach, participatory research, bibliographic research, and as research instruments it was adopted observation, document analysis, identification questionnaire, semi-structured interviews with teachers and focus group conducted with distance tutors. The theoretical framework of the study happens in the light of authors such as, Fernández Cruz (2006), Marcelo Garcia (1999), Kenski (2011, 2013), Marcelo (2009a, 2009b, 2013), Mill (2010, 2012), Silva (2010a, 2010b, 2010c), Tardif (2011), among others. DE appears as a challenging field for university teaching, but it is necessary to recognize that teacher education in and for DE goes far beyond the use of digital information and communication technologies, it requires theoretical and practical thinking about didactic and pedagogical mediation in tune with innovative teaching-learning processes. The interviewed teachers recognize the benefits of DE, but call attention to the need for improving teacher education for this modality. Tutors, even though they are exalted in speeches of teachers, demonstrate several anxieties related to overwork, rework, lack of autonomy, isolated work, action without reflection, recognition and self-recognition weaknesses. Thus, the data analysis showed that, although public policies concerning Open University System demonstrate weaknesses that disadvantage the professional development of DE teachers, teachers and tutors suggest ways that, according to them, can minimize some difficulties.